The secret gospel of Mark : a controversial scholar, a scandalous gospel of Jesus, and the fierce debate over its authenticity /: a controversial scholar, a scandalous gospel of Jesus, and the fierce debate over its authenticity. (2023) - Smith, Geoffrey S (Geoffrey Stephen), 1983-; Landau, Brent
No abstract available